EFEK LAMA PENYINARAN TERHADAP KEBOCORAN TEPI TUMPATAN RESIN KOMPOSIT FLOWABLE - Lestari, Sri (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Exposure duration of light activated composite resin is one of the factors which influenced polimerization level. Polimerization level correlated with the evidence of microleakage . the aim of this study was to evaluate the effect of Exposure Duration Of Light Activated Towards Microleakage Of Restoration Flowable Composit Resin.The samples were made o0f light activated flow able composite resin (Tetric Flow) and the exposure duration was 20 seconds , 40 seconds, 60 seconds. Each group contained of 8 samples of flowable composite resin filling of middle third buccal surface premolar teeth , immersed in methylene blue solution, cut across linguo-buccal and subsequently observed on its edge microleakage using binoculer microscope indicated with the depth of methylene blue penetration. The result showed that edge microleakage from the lowest up to the highest were 40 seconds,60 seconds, 20 seconds. Mann Whitney U statistical analysis only showed significant differences among the 20 seconds group towards 40 seconds group.